Maartje Abbenhuis, An Age of Neutrals: Great Power Politics, 1815-1914 - Samuël Kruizinga (BMGN: Low Countries Historical Review, 2016)
Maartje Abbenhuis, An Age of Neutrals: Great Power Politics, 1815-1914 (Cambridge University Press, 2014, 289 pp., ISBN 987 1 107 03760 1).